METODE COOPERATIVE INTEGRATIF READING AND COMPOSITION (CIRC) DALAM MENINGKATKAN KEMAMPUAN MEMBACA BAHASA JEPANG (Studi Eksperimen pada Peserta Didik Kelas XI IPA SMA Negeri I Anyer Tahun Ajaran 2018/2019) - Nita Marliana, - (2021)
ABSTRAK BAHASA INGGRIS Reading for comprehension (dokkai) is important in Japanese language learning, considering that it is still difficult for students to understand Japanese reading texts. The purpose of this study is to determine the students' reading ability in Japanese using the CIRC method, the students' reading ability in Japanese without using the CIRC method, the difference in reading skills using the CIRC method and those who do not, and quality of CIRC method based on the student's responses in dokkai learning. In connection with the problem that will be raised namely about "CIRC Learning Method on students' reading for comprehension at SMAN 1 Anyer", the type of research used is a type of pure experimental research. To analyze the data using the pretest posttest Group Design control formula. The sample of this study was the grade XI students of SMAN 1 Anyer in the 2018/2019 Academic Year. The instruments used were test and questionnaire. Based on the reseach results, it could be concluded that there was a difference of the students' reading ability in Japanese which used CIRC method with those who do not use the CIRC method. The average score of the students' posttest by using the CIRC method was 59.4, and those who did not use the CIRC method was 48.3. Based on the students' responses in learning reading Japanese by using the CIRC method, it could increase students' interest and motivation in learning. Keywords: Dokkai, CIRC method (Cooperative, Integratif, Reading, and Composition)